The element how finding your passion changes everything - Robinson, Ken 1950-2020 (Tantor Media, 2009)
The element is the point at which natural talent meets personal passion. When people arrive at the Element, they feel most themselves, most inspired, and achieve at their highest levels.
Downloadable audio file. - Title from: Title details screen. - Unabridged. - Duration: 8:02:38
Keywords: Self-actualization (Psychology); Self-realization; Creative ability in children; School failure; Réalisation de soi; Créativité chez l'enfant; Échec scolaire; Downloadable audio books; Audiobooks; Livres audio